2020
DOI: 10.1002/ps.5765
|View full text |Cite
|
Sign up to set email alerts
|

Ten fatty acyl‐CoA reductase family genes were essential for the survival of the destructive rice pest, Nilaparvata lugens

Abstract: BACKGROUND: Fatty alcohols are the precursors of sex pheromone components, wax esters and hydrocarbons in insects. Fatty acyl-CoA reductases (FARs) are important enzymes required for the reduction of fatty alcohol and thereby contribute to the production of cuticular hydrocarbon (CHC).RESULTS: Based on bioinformatics analyses we identified 17 FAR genes in the brown planthopper, Nilaparvata lugens. RNA interference against these genes demonstrated that ten NlFAR genes were essential for the survival of N. lugen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 37 publications
0
30
2
Order By: Relevance
“…This illustrates a much farther-reaching and diverse functionality of insect FARs than previously appreciated. Perhaps most interestingly, knockdown of NlFAR7 also slightly increased gene expression of ACC, whereas NlFAR9 knockdown slightly increased the expression of a FAS gene in N. lugens (Li et al 2020). This revealed previously undiscovered correlations of the expression patterns of CHC biosynthesis genes and warrants further investigation of the underlying gene expression networks.…”
Section: Fatty Acyl-coa Reductase (Far)mentioning
confidence: 66%
See 2 more Smart Citations
“…This illustrates a much farther-reaching and diverse functionality of insect FARs than previously appreciated. Perhaps most interestingly, knockdown of NlFAR7 also slightly increased gene expression of ACC, whereas NlFAR9 knockdown slightly increased the expression of a FAS gene in N. lugens (Li et al 2020). This revealed previously undiscovered correlations of the expression patterns of CHC biosynthesis genes and warrants further investigation of the underlying gene expression networks.…”
Section: Fatty Acyl-coa Reductase (Far)mentioning
confidence: 66%
“…Interestingly, however, a homolog to wat in the brown planthopper Nilaparvata lugens, NlFAR7, is responsible for water-repellent properties of the cuticle and its knockdown resulted in a reduction of overall CHC quantities by almost half (Li et al 2019b, see Table 1). Knockdown of another FAR gene identified in N. lugens, NlFAR9, also reduced CHC levels in adult planthoppers, albeit apparently only affecting longer-chain n-alkanes (above C 26), providing further evidence that chain-lengthspecificity potentially constitutes a common trait in FARs (Li et al 2020).…”
Section: Fatty Acyl-coa Reductase (Far)mentioning
confidence: 77%
See 1 more Smart Citation
“…The fatty acid synthesis initiating enzymes acetyl-CoA Carboxylase (ACC) and fatty acid synthase 3 (FASN3) and the lipophorin receptors LpR1 and LpR2 in D. melanogaster , for instance, have been reported to be essential for CHC production or trafficking and against water-loss ( Wicker-Thomas et al, 2015 ). In addition, in the brown plant hopper Nilaparvata lugens , some fatty acid elongases (ELOs) and reductases (FARs) have been shown to be crucial for correct CHC amounts and desiccation resistance in this rice pest ( Li et al, 2019 , 2020 ). Taken together, these proteins needed for CHC production or trafficking are crucial for water-loss and insecticide-penetration, thereby modulate the ecological adaptability of insects.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, RNAi knockdown of BgFas1 causes a dramatic reduction of methyl-branched CHCs and a slight decrease of straight-chain CHCs [ 29 ]. Our previous studies demonstrated that knockdown of four ELO and two FAR genes resulted in a decrease of CHC amounts in Nilaparvata lugens [ 30 , 31 ]. Furthermore, reduction or elimination concerning the activity of the CYP4G encoded by CYP4G76 and CYP4G115 in N. lugens , DmCYP4G1 in D. melanogaster , LmCYP4G102 in Locusta migratoria , CYP4G19 in Blattella germanica and CYP4G51 in Acyrthosiphon pisum is responsible for the last step of CHC biosynthesis, and provokes a decrease in CHC amounts [ 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%